THE USE OF DUOLINGO TO INCREASE THE STUDENTS’ VOCABULARY MASTERY AT JUNIOR HIGH SCHOOL - Najwa Lahmady; Muh. Yahrif; Muliaty Ibrahim (MERDEKA : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research was to obtain empirical evidence about the effect of using Duolingo to increase students' vocabulary mastery. This research used a quantitative type with a pre-experimental method involving 24 seventh grade students of SMP Nahdiyat Makassar as a research sample. Data collection techniques in this research used a pre-test and a post-test. The results of this research indicate that in the pre-test results the mean value was 56.67 which indicates that the students' ability in the pre-test was still lack while the mean value in the post-test is 67.29 which indicates that students' vocabulary mastery was starting to increase. The results of the data were analyzed using an independent sample t-test, showing that Sig. (2-tailed) was 0.000 which was lower than 0.05 so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Research proves that there was an increase in students' vocabulary mastery through the use of the Duolingo application. Based on the results of this research, it can be concluded that the use of Duolingo can increase the vocabulary mastery of seventh grade students at SMP Nahdiyat Makassar.